Legal Issues Affecting Sustainability of Integrated Coastal Management - Eisma, Rose-Liza V.; Hershman, Marc; Christie, Patrick (Silliman Journal, 2022)
Most integrated coastal management projects that are implemented in developing countries have generally failed to continue after donor support is withdrawn. The Integrated Coastal Management Sustainability Research Project proposes to study, in a multidisciplinary manner, the sustainability of integrated coastal management activities in the Philippines and Indonesia after formal project termination. Legal research is one of the components of this research project. The research aims to: (a) identify the policy, legal, and institutional framework that provides support for the implementation of integrated coastal management, and (b) show the importance of a legal framework and its effective enforcement in sustaining integrated coastal management even after support is gone. This paper will argue that a legal framework and its effective enforcement foster the sustainability of integrated coastal management. Laws, regulations, ordinances, and other legal instruments buttress the sustained implementation of integrated coastal management programs, if they are applied or enforced. In the Philippines, although there are numerous laws that provide policy and regulatory framework for integrated coastal management, these laws are not enforced properly for a variety of reasons. To find out the issues affecting enforcement, field research was conducted in two sites in the Philippines: Mabini, Batangas and Bais Bay, Negros Oriental, Specific interviews with key informants in these sites were conducted. Preliminary results of the qualitative analysis show that because of conflicting policies, confusion of roles, political interference, lack of interest to fully prosecute cases, selective enforcement, and informal enforcement mechanisms, enforcement in the two above-mentioned sites was weak. Due to the ineffective law enforcement as well as inadequate legal regime, integrated coastal management activities floundered after donor support was withdrawn.